Improving Health Targeted Food Quality of Blackberry: Pear Fruit Synergy Using Lactic Acid Bacterial Fermentation - Pucel, Nicholas; Sarkar, Dipayan; Labbe, Ronald G.; Khanongnuch, Chartchai; Shetty, Kalidas (Frontiers in Sustainable Food Systems, 2021)
Blackberry and pear are rich in human health protective phenolic bioactives with high antioxidant activity. These fruits are relevant dietary targets to counter chronic oxidative stress-linked diseases, such as type 2 diabetes (T2D). Due to high perishability, the human health relevant bioactive qualities of such fruits deteriorate during postharvest storage and processing. By improving stability and bioavailability of nutritionally relevant phenolic bioactives during post-harvest stages, effective integration of blackberry and pear as dietary support strategies can be targeted for T2D benefits. Solutions to bioactive quality loss of fruits can be achieved by advancing bioprocessing strategy integrating compatible fruit synergy and beneficial lactic acid bacteria (LAB) based fermentation. This approach was targeted to enhance high levels of phenolic bioactive-linked health quality of blackberry (Rubus spp.) integrated with pear (Pyrus communis) at a ratio of 30:70, which was optimized previously based on potential synergistic effects. The aim of this study was to recruit beneficial LAB such as Lactobacillus helveticus and Bifidobacterium longum to bioprocess previously optimized blackberry: pear synergies to improve phenolic bioactive-linked T2D benefits. Essential health-targeted food quality during bioprocessing was assessed based on total soluble phenolic content, phenolic compound profile, total antioxidant activity, anti-hyperglycemic property relevant α-amylase and α-glucosidase enzyme inhibitory, and anti-hypertensive relevant angiotensin-I-converting enzyme (ACE) inhibitory activities using in vitro assay models. Additionally, potential inhibitory activity of fermented fruit extracts against pathogenic Helicobacter pylori, the common bacterial ulcer pathogen was also investigated. Overall, improvement in the retention and stability of phenolic bioactive content in 30:70 blackberry: pear combination, as well as in 100% juice of both fruit extracts were observed following fermentation. Furthermore, enhanced antioxidant activity, anti-hyperglycemic property relevant α-glucosidase, and anti-hypertensive property relevant ACE enzyme inhibitory activities were also observed in fermented extracts of 30:70 blackberry: pear synergy. Among the substrates only fermentation of 100% blackberry with LAB resulted in inhibitory activity against H. pylori. These results provide the biochemical rationale to develop blackberry: pear fruit synergy and beneficial LAB-based fermentation to improve T2D relevant health benefits while also potentially improving keeping quality.